Farmers’ Attitude towards Adoption of Sustainable Agricultural Practices: A Study in Manipur - Thangjam, Bidyapati; K.K. Jha, K.K. Jha (Indian Journal of Extension Education, 2024)
The farmers’ psychological well-being has an impact on the adoption of sustainable farming practices. The key component involves attitude, which transforms covert behaviour into overt action. This study determined the socio-economic variables that influence farmers’ attitude towards adoption of sustainable agricultural practices. The present study was carried out during 2021-23 in four districts of Manipur state on 320 respondents. In order to gauge the respondents’ attitude, an attitude scale was developed. Linear regression model was applied to investigate the variables that explained attitudes of farmers toward the adoption of sustainable agricultural practices. The findings of the study revealed that majority of respondents exhibited favourable attitude with an attitude index of 70.96. The variables age, family size, education, experience, landholding, extension contacts, social media, market orientation, product orientation, and risk orientation influenced the farmers’ attitudes toward adoption of sustainable agriculturall practices. Developing a feedback channel for farmers to discuss their experiences and difficulties on adoption of technology and formation of farmer’s cooperatives are imperative for bringing improvement in the farmers’ attitude.